The Management of Mathematic Learning Group (A Site Study at SMPN 3 Salatiga) - Prihati, Anik (2011)
The objectives of this research are to describe (1) the material management of Mathematics learning group at Junior High School State 3 Salatiga. (2) The interaction management of Mathematics learning group at Junior High School State 3 Salatiga. (3) The follow up of Mathematics learning group at Junior High School State 3 Salatiga. This is qualitative research and used ethnography design. This research is conducted in Junior High School State 3 Salatiga. The human resources in this research are principal, teacher and student in Junior High School State 3 Salatiga. Data collecting method used interview, observation, and documentation. Data analysis is started from (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Data validity test used credibility, transferability, conformability and dependability. The research's result shows that (1) the material management of Mathematic learning group at Junior High School State 3 is paying attention of student's characteristic. Material is given according to student's development that can be analysis by student, and closed to daily life of student or realistic. The source of material in learning group is derived from various sources such as book from MGMP of mathematic lesson in Salatiga, module, student worksheet, book from Erlangga and Yudistira, and also from out side. (2) The interaction management of Mathematic learning group at Junior High School State 3 Salatiga is done in two directions. Teacher and student made learning group of mathematic based on student's intelligence. Teacher made science foundation to increase interaction in learning group of mathematic by doing learning activity outside classroom and used various learning media. The student is doing assignment according to job divided in group, and executes presentation on the result of group discussion. (3) The follow up management in mathematic learning at Junior High School State 3 Salatiga is according systematical procedure. The follow up activity is done by giving evaluation to the student whether written and practice. The aspect that to evaluate is consisting of 3 aspects that is concept understanding, problem solving, and analysis. Evaluation result of student is analyzed by teacher, for student is who fulfill minimum criteria for completeness so that they can enter enrichment program while the student who did not follow the remedial program.